(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تناولت هذه الدراسة توزع نزر العناصر المعدنية الثقيلة في الرسوبيات الشاطئية لمدينة اللاذقية حيث تم تحديد تراكيزها في 110 عينة من العينات الرسوبية الشاطئية السطحية، تم اعتيانها من سبعة مواقع منتشرة على طول شاطئ مدينة اللاذقية، وذلك خلال الفترة الممتدة ما بين 7 / 5 / 2000 و 21 / 6 / 2001، مستخدمين لذلك جهاز الامتصاص الذري (AAS)، وتم ضبط جودة عمل الجهاز ودقة النتائج، بالاعتماد على تحليل مواد عيارية مرجعية، معتمدة من قبل الوكالة الدولية للطاقة الذرية. تراوحت تراكيز العناصر (Se، Zn، Pb، Cu، Cr وCd) في العينات الرسوبية مابين (0.0137-0.394) μg/g، (13.59-128.17)μg/g، (0.24-5.96)μg/g، (0.13-26.80)μg/g، (14.00-583.94) μg/g و(0.042-0.258) μg/g، على الترتيب، وبمقارنة النتائج السابقة بالقيم العظمى Maximum Permissible Concentration (MAXPC)، وجد أن هذه القيم تقع ضمن الحدود المسموح بها عالمياً، باستثناء عنصر الكروم الذي وصل في بعض المواقع وبعض الجولات إلى قيم أكبر من الحد الأعظمي المسموح به عالمياً. This study deals with the distribution of heavy metals in tidal sediments of Lattakia coast. The concentrations of heavy metals were determined in (110) surface samples of sediments taken from seven tidal sites along Lattakia coast, during the period 7 / 5 / 2000 – 21 / 6 / 2001, using the technique of Atomic Adsorption Spectrophotometric (AAS), and the accuracy of apparatus were done, depending on Certified Reference Materials analysis (CRMs), recommended by International Atomic Energy Agency (IAEA). The concentrations of heavy metals (Cd, Cr, Cu, Pb, Se, Zn) in sediment samples ranged between (0.0137-0.394)μg/g, (13.59-128.17)μg/g, (0.24-5.96)μg/g, (0.13-26.80)μg/g, (0.042-0.258)μg/g and (14.00-583.94)μg/g (dry wt) as follows, and by comparison the prior results with the international (MAXPC) Maximum Permissible Concentration, we found that the values are within the permitted values, except the Chromium element in some seasons and in some stations which reached to higher than the (MAXPC) Maximum Permissible Concentration.